Tính chất của sợi dứa dại (sisal) Việt Nam. - Diệu và cộng sự, Trần Vĩnh (Vietnam Journal of Chemistry, 2014)
In this study, the effect of alkali treatment on the distribution of diameters and tensile strengths of sisal fiber was investigated. The results showed that the distribution of treated fiber diameters was narrowed and tensile strength enormously increased in comparison with untreated fiber. Especially in a smooth condition of the treatment (concentration of alkali solution was 0.1 N, at room temperature, for 72h) the tensile strength of treated sisal fiber was 126% higher than that of untreated one.